2021
DOI: 10.1038/s41419-021-03984-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction induces radioresistance in colorectal cancer by activating [Ca2+]m-PDP1-PDH-histone acetylation retrograde signaling

Abstract: Mitochondrial retrograde signaling (mito-RTG) triggered by mitochondrial dysfunction plays a potential role in regulating tumor metabolic reprogramming and cellular sensitivity to radiation. Our previous studies showed phos-pyruvate dehydrogenase (p-PDH) and PDK1, which involved in aerobic glycolysis, were positively correlated with radioresistance, but how they initiate and work in the mito-RTG pathway is still unknown. Our further genomics analysis revealed that complex I components were widely downregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Shi et al. found that mitochondrial dysfunction can enhance the resistance of COAD to radiotherapy, thus promoting tumor progression ( 25 ). Cheng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al. found that mitochondrial dysfunction can enhance the resistance of COAD to radiotherapy, thus promoting tumor progression ( 25 ). Cheng et al.…”
Section: Discussionmentioning
confidence: 99%
“…PDH complex plays an important role in citric acid cycle and aerobic glycolysis. A recent study suggested that reduced PDH activity can promote cancer cells to repair DNA damages through mitochondrial retrograde signaling [56]. It has recently been found that PKM2 is highly expressed in cancer cells and reshapes cancer metabolic programming.…”
Section: Crosstalk Between Glucose Metabolism and Dna Repair Pathwaysmentioning
confidence: 99%
“…A transient decrease in mitochondrial function has been observed in cancer cell lines shortly after exposure to IR, which correlates with the oxidizing effects of IR [ 132 ] and could be considered for tumor radioresistance. Indeed, colon and lung cancer cells that shift their metabolism to glycolysis because of mitochondria depletion manifest radioresistance [ 133 , 134 ]. On the other hand, an increase in mitochondrial abundance and a high oxidative metabolism have been reported in radioresistant vs. radiosensitive human HNSCC cells [ 135 ].…”
Section: Molecular and Cellular Features Associated With Radioresistancementioning
confidence: 99%